AB0378 Improved clinical outcomes and physical activity in patients with rheumatoid arthritis treated with adalimumab in central and eastern europe. (15th June 2017) - Karateev, D; Codreanu, C; Rojkovich, B; Hojnik, M; Smirnova, E
Abstract : Background: Although physical activity has known positive impacts upon pain, disease activity and functional status in patients with rheumatoid arthritis (RA), very little is known about physical activity in patients with RA on biologic therapy. Objectives: To evaluate the effect of adalimumab treatment on physical activity and relationship with improvements in disease activity and physical function in patients with RA in routine clinical practice. Methods: This was a 52-week multi-center, post-marketing observational study conducted in 7 countries in Central and Eastern Europe (CEE). Eligible RA patients were prescribed originator adalimumab according to the local practice; visits were performed approximately 3 months apart. Physical activity was assessed by validated Short QUestionnaire to ASsess Health-enhancing physical activity (SQUASH)[1, 2], which measures habitual physical activity across four domains: commuting, leisure time and sport, household, work and school. RA disease activity was assessed by DAS28 and physical function by HAQ-DI; clinical remission (REM) and low disease activity (LDA) were defined as DAS28<2.6 and <3.2, respectively. Descriptive statistical analyses were performed, observed data are presented. Results: 462 patients were enrolled and 255 patients completed the study. Mean age was 53.9 (±12.1) yrs; 82.2% of enrolled patients were female; average disease duration was 7.8 (±7.5) yrs. DAS28 decreased from 6.1 (±1.1) at baseline to 2.9 (±1.0) at study end, whereas the mean HAQ-DI from 1.6 (±0.6) to 0.7 (±0.5). The proportion of patients in LDA and REM at study end was 56.0% and 31.1%, respectively. Total SQUASH score increased from 4772 (±4132) to 6104 (±4921), representing 28% improvement in overall physical activity. The largest score improvements were seen in the SQUASH domains of leisure time and sport (by 43%), followed by household activities and activities at work and school (each by 19%). The correlations between the total SQUASH score and its subscores with DAS28 were weak both at baseline and study end. A significant correlation between the total SQUASH and HAQ-DI scores was seen at baseline (r -0.30), but not at the study end (r -0.22). Correlations between SQUASH subscores and HAQ-DI were not significant. The percentage of work disabled subjects decreased from 22% to 17%. According to linear regression analysis, sociodemographic factors did not substantially influence habitual physical activity. Conclusions: Treatment with adalimumab in clinical practice in CEE resulted in clinically meaningful improvements in disease activity and physical function as well as improvements in physical activity. The correlation between the scores for disease activity, physical function and physical activity were however poor and there was no clear influence of the standard sociodemographic factors on physical activity. References: Wendel-Vos WGC. et al. J Clin Epidemiol 2003; 56: 1163–9. Campbell N. et al. J Phys Act Health. 2016;13(2):154–8. Acknowledgements: Funding: The design, study conduct, and financial support for the clinical trial were provided by AbbVie. AbbVie participated in the interpretation of data, drafting, review, and approval of the abstract. Disclosure of Interest: D. Karateev Grant/research support from: Pfizer, Consultant for: Pfizer, Tirupharm, Biocad, Egis, R-Pharm, Novartis, Speakers bureau: Abbvie, Bristol Myers Squibb, Pfizer, Roche, Tirupharm, Biocad, R-Pharm, Novartis, Egis, MSD, UCB, C. Codreanu Grant/research support from: AbbVie, Amgen, BMS, Egis, MSD, Pfizer, Roche, Sanofi, UCB, Consultant for: AbbVie, Amgen, Angellini, Astra Zeneca, BMS, Egis, MSD, Pfizer, Richter, Roche, Sanofi, Servier, Teva, UCB, Zentiva, Speakers bureau: AbbVie, Amgen, Angellini, Astra Zeneca, BMS, Egis, MSD, Pfizer, Richter, Roche, Sanofi, Servier, Teva, UCB, Zentiva, B. Rojkovich Grant/research support from: AbbVie, Amgen, Novartis, Sanofi, UCB, Consultant for: Abbvie, Pfizer, Roche, Speakers bureau: Abbvie, Pfizer, Roche, M. Hojnik Employee of: AbbVie, E. Smirnova Employee of: AbbVie